An Analysis of Informative Speaking on Kakenya Ntaiya’s Speech: A Girl Who Demanded School - Renata Kenanga Rinda; Wahyu Indah Mala Rohmana; Nodistya Septian Indrastana (JETLe (Journal of English Language Teaching and Learning), 2019)
Transferring people idea can be accomplished through informative speaking. There are four types of it which are speaking about objects, processes, events, and concepts. In achieving a good informative speaking, five parameters should be fulfilled which are do not overestimate what the audience knows, relate the subject directly to the audiences, do not be too technical, avoid abstractions, and personalize the idea of the speakers. Dealing with that, this paper aimed at analyzing the types of Kakenya Ntaiya’s Speech entitled A Girl Who Demanded School and describing its content with the five parameters of good informative speaking mentioned previously. Descriptive analysis was implemented with video recording transcription as the data source. The findings show that Kakenya Ntaiya spoke about events. By the end, it is concluded that her speech mets the five criteria of good informative speaking.